Grid-connected lithium-ion battery energy storage system: A bibliometric analysis for emerging future directions. (1st February 2022) - Wali, S.B.; Hannan, M.A.; Ker, Pin Jern; Rahman, MS Abd; Mansor, M.; Muttaqi, K.M.; Mahlia, T.M.I.; Begum, R.A.
Abstract: The lithium-ion battery energy storage systems (ESS) have fuelled a lot of research and development due to numerous important advancements in the integration and development over the last decade. The main purpose of the presented bibliometric analysis is to provide the current research trends and impacts along with the comprehensive review in the field of the grid-connected lithium-ion battery (LIB) ESS within the year 2010–2021. The research has been performed using refined keyword searches on grid-connected LIB ESS in the Scopus database and the data of the top 100 highly cited articles were extracted. The research trend has shown that the grid-connected LIB ESS literature has increased substantially between 2016 and 2021, compared to the period 2010–2015. The bibliometric analysis consists of detailed keyword co-occurrence network analysis, co-authorship map, distribution of articles over countries, journals, research types, and subject categories. The evaluation of highly cited articles identifies numerous aspects, including methodologies and systems, issues, and challenges, to determine existing constraints and research gaps. The process of deciding, developing, and evaluating the highly cited articles, is expected to contribute to a methodical foundation for potential progress of grid-connected LIB ESS, as well as identify emerging pathways for future researchers. This study may act as a guideline providing future directions towards improving energy efficiency, environmental sustainability, reliability, and flexibility of the LIB ESS integrated power system. Highlights: Highly cited literatures are considered for analyzing battery energy storage systems. Identified and analyzed the highly cited articles to guide future LIB research. Factors, issues and challenges for future LIB energy storages are highlighted. LIB storage research trends and impacts are analyzed for sustainable energy. This study may act as a guideline for future BESS novel research and development.